THE INFLUENCE OF PARENTS' DEMOCRATIC COMMUNICATION PATTERNS ON STUDENT LEARNING MOTIVATION IN SENIOR HIGH SCHOOL N 6 JAMBI CITY - Manalu, Jentina Rospita Dewi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2025)
Motivation is an essential factor that drives individuals to achieve their goals. For students, learning motivation plays a crucial role in enhancing the quality of learning to reach academic success and future aspirations. One of the key factors influencing learning motivation is the communication pattern applied within the family. Each family has different communication dynamics, which may lead to variations in students’ learning motivation. This study aims to examine the influence of parents’ democratic communication patterns on students’ learning motivation at SMA Negeri 6 Jambi City. The research employed a quantitative approach with data collected through questionnaires and analyzed using the t-test assisted by SPSS software. The results show a significance value of 0.002 (<0.05) and a t-count of 3.251 (>2.000). Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, indicating a significant influence of parents’ democratic communication patterns on students’ learning motivation.